Inhibition of T-cell activity in alopecia areata: recent developments and new directions - Passeron, Thierry; King, Brett; Seneschal, Julien; Steinhoff, Martin; Jabbari, Ali; Ohyama, Manabu; Tobin, Desmond J.; Randhawa, Simran; Winkler, Aaron; Telliez, Jean-Baptiste; Martin, David; Lejeune, Alexandre (Frontiers in Immunology, 2023)
Alopecia areata (AA) is an autoimmune disease that has a complex underlying immunopathogenesis characterized by nonscarring hair loss ranging from small bald patches to complete loss of scalp, face, and/or body hair. Although the etiopathogenesis of AA has not yet been fully characterized, immune privilege collapse at the hair follicle (HF) followed by T-cell receptor recognition of exposed HF autoantigens by autoreactive cytotoxic CD8 + T cells is now understood to play a central role. Few treatment options are available, with the Janus kinase (JAK) 1/2 inhibitor baricitinib (2022) and the selective JAK3/tyrosine kinase expressed in hepatocellular carcinoma (TEC) inhibitor ritlecitinib (2023) being the only US Food and Drug Administration-approved systemic medications thus far for severe AA. Several other treatments are used off-label with limited efficacy and/or suboptimal safety and tolerability. With an increased understanding of the T-cell-mediated autoimmune and inflammatory pathogenesis of AA, additional therapeutic pathways beyond JAK inhibition are currently under investigation for the development of AA therapies. This narrative review presents a detailed overview about the role of T cells and T-cell-signaling pathways in the pathogenesis of AA, with a focus on those pathways targeted by drugs in clinical development for the treatment of AA. A detailed summary of new drugs targeting these pathways with expert commentary on future directions for AA drug development and the importance of targeting multiple T-cell-signaling pathways is also provided in this review.